Root Canal Configuration Using Cone Beam Computed Tomography in Mandibular Incisors of Pakistani Individuals: Root Canal Configuration Using Cone Beam Computed Tomography in Mandibular Incisors - Shakeel, Sadia; Fahim, Ayesha; Tariq, Khaloud; Haider, Irsam; ur Rehman, Ijaz; Anwar, Malik Adeel; Chaudhry, Ammara (Pakistan Journal of Health Sciences, 2024)
A thorough understanding of root canal morphology is crucial for successful endodontic therapy. Variations in root canal anatomy, including differences in configuration and disposition, can significantly affect treatment outcomes, emphasizing the importance of population-specific investigations. Objectives: To assess and identify anatomical variations in the root canal morphology of mandibular incisors among Pakistani individuals using cone beam computed tomography imaging. Methods: In this retrospective cross-sectional study, 440 cone beam computed tomography scans of mandibular incisors from 115 patients were analyzed. Data on patient demographics (age and gender), tooth characteristics (central or lateral incisors), root count, and root canal morphology were recorded. Statistical analysis using Chi-squared and Kruskal-Wallis tests was performed to explore associations between demographic variables and root canal configurations. Results: Out of 115 patients, 110 cone beam computed tomography scans were included, while five were excluded due to missing teeth. The mean age of participants was 36.49 years, with a gender distribution of 43.6% female and 56.4% male. Type I and Type III configurations were the most prevalent. Statistically significant gender differences were found in lateral incisors (p<0.01), with male more frequently exhibiting Type III configurations in central incisors, while female displayed Type I configurations in lateral incisors. No significant age-related differences were observed. Conclusions: It was concluded that mandibular incisors in Pakistani individuals exhibit notable anatomical variations, primarily Type I and Type III configurations. These findings underscore the importance of using advanced imaging tools like bone beam computed tomography for population-specific studies, enabling more tailored and effective endodontic treatments.